ANIMASI INTERAKTIF SIMULASI TES BUTA WARNA DENGAN METODE ISHIHARA BERBASIS ADOBE FLASH CS 5: Deni Ambari; Fitri Latifah - Jurnal, Redaksi Tim (PETIR, 2018)
Colour blindness isi disorder caused by the inability of teh eys cone cells to capture a spesific color spectrum due to genetic factors. Color blindness is a genetic disorder/ congenital inherited from parents to their childern, because this disorder is carried by the X chomeosome. Many people find out too late in the color blindness.This isi due to lack of information and insight about the color blind test. Therefore, this aplication is made so that people can find out about all sort of color blindness test, the results of each simulation to make simulation aktratif silmulation is made with adobe cs 5